The complementary exponential power lifetime model - Barriga, Gladys Dorotea Cacsire [UNESP]; Louzada-Neto, Franscisco; Cancho, Vicente G. (Elsevier B.V., 2011)
In this paper we propose a new lifetime distribution which can handle bathtub-shaped unimodal increasing and decreasing hazard rate functions The model has three parameters and generalizes the exponential power distribution proposed by Smith and Bain (1975) with the inclusion of an additional shape parameter The maximum likelihood estimation procedure is discussed A small-scale simulation study examines the performance of the likelihood ratio statistics under small and moderate sized samples Three real datasets Illustrate the methodology (C) 2010 Elsevier B V All rights reserved
Keywords: Exponential power distribution; Bathtub shaped hazard function; Unimodal hazard function; Lifetime data